Exploring the organic harmony of the modern pentathlon of sports - Han, D. (Journal of The Korea Society of Computer and Information, 2020)
What sports have in common is that they must use their bodies to play and lead to victory. The use of the body differs in many ways depending on the event, which part should be used as the focus.The commonality of all sports is that sports can achieve the best results by using and using parts of the body in harmony. The use of strength or muscles varies depending on the type of sport or the type of sport, so the use of the body or the results of athletic events also varies. Sports are premised on the organic use of the body, but the implications of sports can be found in that the degree of organic use does not apply equally to all sports. Sports demand organic balance and flexibility. Depending on the type of sport, you can explore which organic harmony produces more effective effects and find out which events are more beneficial to the human body.This study aimed to find out whether the organic harmony of the body actively contributes to the development of sports and a healthy mental culture. In this study, we proposed the hypothesis that the modern Pentathlon will induce the most desirable organic harmony as a global Olympic sport, and tried to verify that the hypothesis is valid and verifiable. In order to do this study, I tried to find out the organic viewpoints centered on the Miletos school, re-examine the meaning of the modern Pentathlon of games as an Olympic event, and conduct organic harmony and exploration of the modern Pentathlon of games in terms of sports.